2016
DOI: 10.1002/acr.22868
|View full text |Cite
|
Sign up to set email alerts
|

Defining an International Standard Set of Outcome Measures for Patients With Hip or Knee Osteoarthritis: Consensus of the International Consortium for Health Outcomes Measurement Hip and Knee Osteoarthritis Working Group

Abstract: ObjectiveTo define a minimum Standard Set of outcome measures and case‐mix factors for monitoring, comparing, and improving health care for patients with clinically diagnosed hip or knee osteoarthritis (OA), with a focus on defining the outcomes that matter most to patients.MethodsAn international working group of patients, arthroplasty register experts, orthopedic surgeons, primary care physicians, rheumatologists, and physiotherapists representing 10 countries was assembled to review existing literature and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
93
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(94 citation statements)
references
References 44 publications
1
93
0
Order By: Relevance
“…Unfortunately, inconsistency in outcome reporting and incomplete data reporting still limited the number of studies that could be included in statistical analysis to fewer than half. It is hence recommended that a validated standard set of outcome measures be implemented for future studies, such as those already available in hip and knee pain . This would eliminate the variability in outcome measures and allow pooling of data across more studies.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, inconsistency in outcome reporting and incomplete data reporting still limited the number of studies that could be included in statistical analysis to fewer than half. It is hence recommended that a validated standard set of outcome measures be implemented for future studies, such as those already available in hip and knee pain . This would eliminate the variability in outcome measures and allow pooling of data across more studies.…”
Section: Discussionmentioning
confidence: 99%
“…Quality of life is based on a personal perception of one's own health status (Fusco et al, 2011). Despite this fact, Rolfson et al (2016) identified that EQ-5D has a clear potential for application for measure of clinical impact of interventions in the elderly (Rolfson, 2016). There are some studies mentioned in this review that have attempted to establish a minimally important difference be-…”
Section: Discussionmentioning
confidence: 99%
“…These combined sets have already been developed for several conditions, including lower back pain, 6 advanced prostate cancer 7 and hip and knee osteoarthritis. 8 no doubt that these are important, but as O'Mahony and colleagues point out, implementation of the framework will require further review and validation of these outcomes by patient groups, including those from low and middle-income countries. 12 Then, these outcomes should be measured appropriately.…”
Section: Functional Outcomes Andmentioning
confidence: 99%
“…The second step is to establish so‐called minimum outcomes sets or core sets of outcomes (both clinical and patient‐reported). These combined sets have already been developed for several conditions, including lower back pain, advanced prostate cancer and hip and knee osteoarthritis . With the help of Delphi‐like processes and involvement of both patients and different clinical specialists, organizations such as the International Consortium for Health Outcomes Measurement (ICHOM) and the Core Outcome Measures in Effectiveness Trials (COMET) focus on defining outcomes that matter most to patients and that are to be used as effectiveness endpoints in clinical trials, with the patient's voice becoming increasingly important …”
mentioning
confidence: 99%